Black Soldier Fly Larvae Meal as a Sustainable Alternative to Fishmeal in Juvenile Swamp Eel Diets: Effects on Growth and Meat Quality - Nhien Thi Nguyen; Nam Hoang Tran (Aquaculture Journal)
The rising scarcity and cost of fishmeal due to overfishing and environmental challenges demand alternatives. Black soldier fly (Hermetia illucens) larvae (BSFL) meal, with its nutritional value, shows promise as a sustainable supplement for aquaculture species. This study evaluated the effects of BSFL meal supplementation on growth performance, survival, feed conversion efficiency, and meat quality in juvenile swamp eels (Monopterus albus) initially weighing 4.0 ± 0.5 g. The eels were fed diets with 0% (control), 10%, 30%, and 50% BSFL meal for three months. Growth performance was assessed using the absolute growth rate (AGR) and the specific growth rate (SGR). Feed conversion ratios (FCRs), survival rates, and meat quality metrics, including fillet percentage, crude protein, and moisture content, were analyzed. Statistical differences among groups were evaluated using one-way ANOVA followed by Tukey’s post hoc test for pairwise comparisons. The 30% BSFL group exhibited superior performance, achieving the highest AGR and SGR (p < 0.05) and the lowest FCR (2.33 ± 0.03). Fillet percentage was highest in this group (27.3% ± 0.7%), with no significant differences in crude protein or moisture content. Survival rates were consistent across treatments (75.2–76.0%, p > 0.05). These results confirm that 30% BSFL supplementation optimally enhances productivity and meat quality in swamp eels, highlighting BSFL meal’s potential as a sustainable aquafeed alternative.